AIP--aterogenní index plazmy jako významný prediktor kardiovaskulárního rizika: od výzkumu do praxe - Dobiásová, M (Vnitrni lekarstvi, 2006)
BACKGROUND: Various indices have been used for the diagnosis and prognosis of cardiovascular disease (CVD). Atherogenic index of plasma (AIP) is a logarithmically transformed ratio of molar concentrations of triglycerides to HDL-cholesterol. The strong correlation of AIP with lipoprotein particle size may explain its high predictive value. Here we summarize data on AIP calculated in 8394 subjects from 6 population and clinical studies. RESULTS: AIP values increase with increasing CV risk. Thus umbilical cord, young children, healthy women have values below 0.1 while men and subjects with CV risk factors such as hypertension, diabetes, dyslipidemia have increasing values up to 0.4. Based on these data we suggest that AIP values of -0.3 to 0.1 are associated with low, 0.1 to 0.24 with medium and above 0.24 with high CV risk. In the population study men had higher AIP values than women. In a cohort undergoing coronary angiography AIP, in model that included age, BMI, waist circumference, type 2. DM, blood pressure, smoking, TG, TC, LDL-C, apoB, HDL-C, and TC/HDL-C, AIP was the best predictor of positive findings. AIP was also a highly sensitive marker of differences of lipoprotein profiles in families of patients with premature myocardial infarction and control families. Treatment with ciprofibrate, and combination of statin and niacin dramatically decreased AIP. Combination with hypoglycemic therapy that included pioglitazone decreased AIP in patiens with type 2. diabetes. CONCLUSIONS: AIP can be easily calculated from standard lipid profile. As a marker of lipoprotein particle size it adds predictive value beyond that of the individual lipids, and/or TC/HDL-C ratio.
Keywords: rizikové faktory; Triglycerides; kardiovaskulární nemoci; Cholesterol, HDL; triglyceridy; Humans; ateroskleróza; Cardiovascular Diseases; Predictive Value of Tests; lidé; Atherosclerosis; prediktivní hodnota testů; Particle Size; HDL-cholesterol; Risk Factors; velikost částic